Xenograft Enriched with Autologous Bone Marrow in Inlay Reconstructions: A Tomographic and Histomorphometric Study in Rabbit Calvaria - de Oliveira e Silva, Marcelo; Pelegrine, André Antonio; Alves Pinheiro da Silva, Alexandre; Manhães Júnior, Luiz Roberto; de Mello e Oliveira, Rafael; Gaiba França, Silvana; Aloise, Antonio Carlos; Ferreira, Lydia Masako (International Journal of Biomaterials, 2012)
Objective. The aim of this study was to evaluate the bone healing after the usage of a scaffold enriched with bone marrow. Study Design. Ten rabbits were divided into 2 groups of 5 animals. Bilateral 12 mm diameter defects were created in the parietal bones. In control group Bio-Oss were inserted in both defects and, in experimental group, Bio-Oss enriched with autologous bone marrow were inserted in both defects. In these two groups, one of the calvarial defects was covered with Bio-Gide. The rabbits were sacrified 8 weeks after surgery and both CT and histomorphometric analysis were done. Results. The CT showed a lower remaining defect area in the experimental group covered with Bio-Gide when compared with control group, with and without Bio-Gide. The histomorphometrics showed no difference between groups regarding the non-vital mineralized tissue area. For vital mineralized tissue area, the experimental group covered with Bio-Gide obtained a higher percentage area when compared with control group, with and without Bio-Gide. For non-mineralized tissue area, the experimental group covered with Bio-Gide obtained a lower percentage area when compared with control group, with and without Bio-Gide. Conclusion. Both autologous bone marrow and membrane can contribute to the enhancement of bone healing.